Urinary Fructose-1,6-Bisphosphatase (FBP-1,6) and N-Acetyl-β-Hexosaminidase (HEX) in Monitoring Kidney Transplantation - Literature Review - Kępka, Alina; Szajda, Sławomir Dariusz; Waszkiewicz, Napoleon; Chojnowska, Sylwia; Pludowski, Paweł; Ładny, Jerzy Robert; Zwierz, Krzysztof (IntechOpen, 2011)
None